1979
DOI: 10.1107/s0567740879004143
|View full text |Cite
|
Sign up to set email alerts
|

Nouvelle détermination de la structure cristalline du μ-oxo-bis[pentachlororuthénate(IV)] de potassium, K4[Ru2Cl10O] et affinement de la structure de l'hexachlororuthénate de potassium K2[RuCl6]

Abstract: Crystals of K4[Ru2CII00] are tetragonal, space group I4/mmm with a = 7.097 (2), c = 17.015 (3) A and Z = 2. The structure was first determined by Mathieson, MeUor & Stephenson [Acta Cryst. (1952). 5, 185-186] from a zero-level Weissenberg photograph for the formula K4[Ru2CII00].H20. New intensities were collected on an automatic four-circle diffractometer with Mo Kff radiation, and anisotropic full-matrix leastsquares refinement was performed. The final R was 0.034 for the 245 measured reflexions. This refin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 3 publications
2
8
1
1
Order By: Relevance
“…The crystal structures of the alkali‐metal and ammonium hexahaloruthenates(IV) have not been reported, except for those K 2 RuCl 6 [34] and (NH 4 ) 2 RuCl 6 [32] . Furthermore, while electronic structure calculations have suggested optical tuning through the A cation and the halide in related vacancy‐ordered double perovskites, [15, 35] there has been no experimental demonstration of this effect with respect to the A cation.…”
Section: Figurementioning
confidence: 99%
“…The crystal structures of the alkali‐metal and ammonium hexahaloruthenates(IV) have not been reported, except for those K 2 RuCl 6 [34] and (NH 4 ) 2 RuCl 6 [32] . Furthermore, while electronic structure calculations have suggested optical tuning through the A cation and the halide in related vacancy‐ordered double perovskites, [15, 35] there has been no experimental demonstration of this effect with respect to the A cation.…”
Section: Figurementioning
confidence: 99%
“…Previous investigations of MCl 2 ±RuCl 3 systems (M = K and Cs) have led to the identi®cation of K 4 [Ru 2 Cl 10 O] (Deloume et al, 1979) and Cs 4 Ru 2 Cl 10 O (Santana Da Silva et al, 1999). We have investigated the hydrated systems MCl 2 ±RuCl 3 ±H 2 O (M = Mg, Ca and Ba) and, just recently, have determined the structure of Mg 2 Ru 2 Cl 10 OÁ16H 2 O (Boufas et al, 2007).…”
Section: Commentmentioning
confidence: 99%
“…Interestingly, few other derivatives of [Ru 2 Cl 10 O] 4À are known. The only previous structure reports are for K 4 Ru 2 Cl 10 O (Deloume et al, 1979) and Cs 4 Ru 2 Cl 10 O (Santana Da Silva et al, 1999), where Ru IV is present with anhydrous alkali ions. One goal of the present work was therefore to examine the nature of the interactions between the [Ru 2 Cl 10 O] 4À anion and hydrated cations capable of forming hydrogen bonds.…”
Section: Commentmentioning
confidence: 99%
“…In the latter case, the structure was ®rst determined (Mathieson et al, 1952) from a zerolevel Weissenberg photograph for the formula K 4 Ru 2 Cl 10 OÁ-H 2 O. A subsequent fully anisotropic re®nement (R = 0.034 for 245 measured re¯ections) has shown that there is, in fact, no water molecule in the structure (Deloume et al, 1979). The correct formula is therefore K 4 Ru 2 Cl 10 O.…”
Section: Commentmentioning
confidence: 99%